2017
DOI: 10.3892/ol.2017.6567
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of speckle-type POZ protein for the prediction of poor prognosis in patients with non-small cell lung cancer

Abstract: Speckle-type POZ domain protein (SPOP) has been acknowledged as a tumor suppressor gene in numerous types of cancer. However, SPOP expression and its prognostic role in human non-small cell lung cancer (NSCLC) remain unknown. The present study investigated SPOP expression in NSCLC and evaluated its prognostic significance in patients with NSCLC. The results demonstrated that SPOP expression was significantly downregulated in NSCLC tissues at the mRNA and protein level compared with normal lung tissues using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Our previous study found that the expression of SPOP was significantly inhibited in NSCLC tissues compared with that in normal tissues [22]. To determine whether the low SPOP expression in NSCLC is caused by DNA hypermethylation, our study searched the Human Genome Database for the presence of CpG islands in the SPOP promoter using Online software (http://www.urogene.org/methprimer) and found some CpG islands in the vicinity of the transcription start site (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study found that the expression of SPOP was significantly inhibited in NSCLC tissues compared with that in normal tissues [22]. To determine whether the low SPOP expression in NSCLC is caused by DNA hypermethylation, our study searched the Human Genome Database for the presence of CpG islands in the SPOP promoter using Online software (http://www.urogene.org/methprimer) and found some CpG islands in the vicinity of the transcription start site (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the regulation mechanism of SPOP expression in NSCLC is still unclear [21]. Intriguingly, our pre-experiment found that SPOP was obviously inhibited in NSCLC tissues compared with that in adjacent normal lung tissues [22], suggesting that SPOP functions as a cancer suppressor gene (TSG). Additionally, Kim et al revealed that SPOP somatic mutations were not harbored in solid tumors, indicating that somatic mutations and decreased SPOP expression might be separate events in NSCLC [20].…”
Section: Introductionmentioning
confidence: 99%
“…[14] The same prognostic result was observed in NSCLC, and the downregulation of SPOP expression contributed to poor tumor differentiation and LNM. [11] Additionally, the expression level of SPOP, identified as a prognosis-related biomarker, was significantly lower in CRC tissues than adjacent normal tissues. [13] Although the majority of studies focused on the potential evidence indicating an unfavorable impact of low SPOP expression on clinical outcome, the prognostic value of SPOP in cancer patients is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…LC is one of the leading causes of cancer-related death in the world [82]. Downregulation of SPOP has been observed in non-small cell LC (NSCLC) tissues compared with normal tissues at both the transcriptional and translational levels [83]. Furthermore, the level of SPOP was confirmed to be associated with several clinicopathologic parameters, and a decrease in SPOP was considered a predictor of poor prognosis in patients with NSCLC, suggesting that SPOP could be a potential tumor suppressor in LC [83].…”
Section: Lung Cancer (Lc)mentioning
confidence: 99%
“…Downregulation of SPOP has been observed in non-small cell LC (NSCLC) tissues compared with normal tissues at both the transcriptional and translational levels [83]. Furthermore, the level of SPOP was confirmed to be associated with several clinicopathologic parameters, and a decrease in SPOP was considered a predictor of poor prognosis in patients with NSCLC, suggesting that SPOP could be a potential tumor suppressor in LC [83]. The sirtuin (SIRT) family of NAD-dependent protein lysine deacylases has been reported to participate in multiple biological processes such as transcription regulation, metabolism and DNA repair [84][85][86].…”
Section: Lung Cancer (Lc)mentioning
confidence: 99%